First report of root rot on onion (Allium cepa) seedlings caused by Globisporangium irregulare in South Korea. Issue 2 (4th March 2023) - Choi, Okhee; Kang, Byeongsam; Lee, Yeyeong; Kwon, Jin-Hyeuk; Kim, Jinwoo
Abstract: Severe root rot was observed in onion seedlings growing in nursery seedbeds in Changnyeong, South Korea in September 2021. The diseased onion seedlings showed symptoms including water-soaking, browning and blight, followed by seedling collapse. Three isolates were obtained from diseased onion seedlings, and their morphological characteristics were found to be similar to previously described Pythium species. Artificial inoculation with isolates produced identical symptoms to those observed in the original infection. Based on morphological characteristics, sequencing of rRNA gene internal transcribed spacer, ribosomal large subunit gene region, and cytochrome c oxidase subunit I gene region, and pathogenicity testing, the causative agent of root rot on the onion seedlings was identified as Globisporangium irregulare (formerly Pythium irregulare ). This is the first report of root rot caused by G. irregulare on onion seedlings in Korea. The results of this study suggest that root rot may pose a severe threat to onion seedling cultivation.